Revolusi Digital: Peran Teknologi Elektro Dalam Mengubah Cara Kita Hidup dan Bekerja - Saputra, Daiva Tsusayya Surya; Aryasatya, Muhamad Nazhif; Faja, Rangga Dwi; Fuadin, Ahmad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The digital revolution fueled by advances in electro-technology has fundamentally changed the way we live and work. This article examines the important role electro-technology has played in facilitating these changes, with a focus on its impact on everyday life and the world of work. We discuss recent innovations in electro-technology such as artificial intelligence, and the Internet of Things, and analyze how these changes affect the way we communicate, shop and get healthcare. In addition, we explain the transformation of the employment landscape, including the automation of processes, changes in skill requirements and the emergence of new working models. The challenges faced in effectively adopting electro-technology, as well as the opportunities it opens up for innovation and economic growth, are also discussed. Finally, the article reflects on the social, cultural, and ethical implications of using electro-technologies, including issues of privacy, data security, and unequal access to technology.